“Why Is This About Dostoevsky?” Or On the Vicissitudes of the Restoration of Darovoe - Albina S. Bessonova; Vladimir A. Viktorovich (Достоевский и мировая культура: Филологический журнал, 2022)
The fourth of a series of articles dedicated to the restoration and museification of the memorial space of Darovoe — Monogarovo — Cheremoshnya. Dostoevsky’s Darovoe Museum-Estate opened anew on November 20th, 2021, while the restoration of the Church of the Descent of the Holy Spirit is still running. The authors of the article concentrate on the pressing issues of the ongoing processes and suggest reflecting on the basic principles ruling contemporary Russian restorers. The directives of the “Venice Charter” (1964), when absolutized, lead as in this case to the destruction of authenticity. Instead of Dostoevsky’s estate, we end up with Ivanov’s, and instead of the Church Dostoevsky looked at, we canonize the architectural preferences of the archpriest of the Church at the beginning of the 20th century. Of particular concern is the fate of the Linden Grove, now on the edge of disappearance. The causes of the losses we are witnessing are academic as well as social and moral.